The Criminal Law Enforcement Against the Use of Fake Identities in Medical Practice - Putra Sedana, Agus; Indar, Indar; Muchtar, Syamsuddin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
This study aims to analyze criminal law enforcement against the use of fake identities as doctors. The type of research used is empirical legal research. There are 2 types of data obtained, namely the first primary data obtained through interviews, the second secondary data, namely laws, books and journals. The research locations were centered at the Makassar District Court, the South Sulawesi High Prosecutor's Office, the South Sulawesi Regional Police and the Makassar City Branch of the Indonesian Doctors' Association. The results of the data that have been obtained were analyzed qualitatively and presented descriptively. The results of the study show that: Criminal Law enforcement against the use of false identities as doctors in carrying out medical practices has not been maximized, while the influencing factors are law enforcement factors where law enforcement officials do not understand and master the regulations, community factors are the community ignore to report practice of fake doctors.